How to think on moral issues? Richard Mervyn Hare’s conception - Ślęczek-Czakon, Danuta (Folia Philosophica, 2011)
The paper deals with moral theory by Richard Mervyn Hare (1919-2002), British philosopher and meta-ethicist, who searched for the moral thinking in setting the agreement between formalism and utilitarianism. Having discussed basic axioms of Hare’s prescriptivism the author discusses it critically.